2021
DOI: 10.3348/kjr.2020.1227
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Digital Breast Tomosynthesis for Detecting Breast Cancer in the Diagnostic Setting: A Systematic Review and Meta-Analysis

Abstract: Objective To compare the accuracy for detecting breast cancer in the diagnostic setting between the use of digital breast tomosynthesis (DBT), defined as DBT alone or combined DBT and digital mammography (DM), and the use of DM alone through a systematic review and meta-analysis. Materials and Methods Ovid-MEDLINE, Ovid-Embase, Cochrane Library and five Korean local databases were searched for articles published until March 25, 2020. We selected studies that reported di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
(131 reference statements)
0
14
0
1
Order By: Relevance
“…Briefly, 18 studies (14 univariate and four bivariate) were systematic reviews with meta-analyses [ 14 15 19 20 21 22 23 24 25 26 27 28 29 31 32 33 34 35 ] and six studies were systematic reviews without meta-analyses [ 16 17 18 30 36 37 ]. In terms of the type of data used for analyses, 13 studies used dichotomous data to measure the following outcomes: 1) efficacy or safety of an intervention (proportion of tumor response, recurrence, or treatment-related complications), 2) efficacy of a diagnostic test (proportion of technical failure and unreliable measurement), 3) imaging features in a certain disease (proportion of specific imaging findings), 4) evaluation of study quality or reporting quality (proportion of studies that met the specific criteria), and 5) diagnostic yield [ 14 15 18 19 22 23 24 28 32 33 34 35 36 ]; six studies used time-to-event data to calculate the efficacy of a new intervention or the reliability between overall survival and imaging surrogate markers [ 15 22 31 32 33 34 ]; six studies used diagnostic test data to pool the diagnostic performance of index tests [ 16 25 26 27 29 37 ]; two studies used continuous data to evaluate the agreement and reliability of measurements between imaging methods [ 20 21 ]; one study used descriptive data from imaging protocols in randomized controlled trials of acute ischemic stroke [ 30 ]; and one study used qualitative and quantitative data to assess the health-related quality-of-life in patients with hepatocellular carcinoma [ 17 ]. The number of included studies ranged from 4 to 516, with the majority (83%, 20 out of 24) of the articles including more than 10 studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, 18 studies (14 univariate and four bivariate) were systematic reviews with meta-analyses [ 14 15 19 20 21 22 23 24 25 26 27 28 29 31 32 33 34 35 ] and six studies were systematic reviews without meta-analyses [ 16 17 18 30 36 37 ]. In terms of the type of data used for analyses, 13 studies used dichotomous data to measure the following outcomes: 1) efficacy or safety of an intervention (proportion of tumor response, recurrence, or treatment-related complications), 2) efficacy of a diagnostic test (proportion of technical failure and unreliable measurement), 3) imaging features in a certain disease (proportion of specific imaging findings), 4) evaluation of study quality or reporting quality (proportion of studies that met the specific criteria), and 5) diagnostic yield [ 14 15 18 19 22 23 24 28 32 33 34 35 36 ]; six studies used time-to-event data to calculate the efficacy of a new intervention or the reliability between overall survival and imaging surrogate markers [ 15 22 31 32 33 34 ]; six studies used diagnostic test data to pool the diagnostic performance of index tests [ 16 25 26 27 29 37 ]; two studies used continuous data to evaluate the agreement and reliability of measurements between imaging methods [ 20 21 ]; one study used descriptive data from imaging protocols in randomized controlled trials of acute ischemic stroke [ 30 ]; and one study used qualitative and quantitative data to assess the health-related quality-of-life in patients with hepatocellular carcinoma [ 17 ]. The number of included studies ranged from 4 to 516, with the majority (83%, 20 out of 24) of the articles including more than 10 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Seven articles [ 16 24 27 30 31 32 36 ] did not report how many reviewers participated in the evaluation of study eligibility or whether they worked independently (item #8). Eighteen articles [ 16 17 18 19 20 21 22 23 24 25 26 27 28 29 32 34 36 37 ] did not cite the studies that seemed to meet the inclusion criteria, but were excluded in the final stage or did not explain the reason for exclusion (item #16b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these advances, major problems remain in imaging of dense and thick breasts at acceptable radiation doses. Research in recent years has shown that DBT can more accurately assess breast cancer size and stage than conventional mammography [3]. It has been shown to improve the detection rate of cancers in women with dense breasts when using supplemental tomosynthesis in addition to standard digital mammography and has comparable sensitivity in the detection of noncalcified breast lesions when compared with digital mammography carried out with additional views.…”
Section: Introductionmentioning
confidence: 99%